Use of 16S rRNA Gene Profiling by Terminal Restriction Fragment Length Polymorphism Analysis To Compare Bacterial Communities in Sputum and Mouthwash Samples from Patients with Cystic Fibrosis - Rogers, G.B; Carroll, M.P; Serisier, D.J; Hockey, P.M; Jones, G; Kehagia, V; Connett, G.J; Bruce, K.D (Journal of Clinical Microbiology, 2006)
The bacterial communities present in the oral cavity and the lungs of 19 adult cystic fibrosis (CF) patients were compared by using terminal restriction fragment length polymorphism analysis of 16S rRNA gene PCR products amplified from nucleic acids extracted directly from bacteria in clinical samples. Sputum samples were not found to be subject to profound contamination by oral cavity bacteria. Evidence of colonization of the CF lung by certain oral bacterial species was found.